STRATEGI PEMASARAN GULA SEMUT DI KABUPATEN ROKAN HULU PROVINSI RIAU - Evy Maharani; Yeni Kusumawaty (Indonesian Journal of Agricultural Economics, 2010)
Currently, granulated palm sugar (palm suiker) with local name “gula semut” becameknown and generally produced for export market and partly for domestic food industry.Great market prospects for granulated palm sugar can not be utilized by communitybecause majority of producers make solid (molded) palm sugar. In the district of RokanHulu, granulated palm sugar is only produced by one producer. This research is a casestudy of granulated palm sugar producer with the aims to study: (1) marketing strategyof granulated palm sugar; (2) external and internal marketing factors, and (3) alternativemarketing strategy. Analysis of qualitative description is to describe the marketing ofgranulated palm sugar in the form of marketing mix (product, price, promotion anddistribution). A quantitative analysis carried out to develop a marketing strategy withSWOT analysis. Conclusions of research: (1) product strategy of granulated palm sugaris applied through packaging attributes of halal label, barcode, license, product benefits,and area of origin; (2) the price of the sugar is Rp 30,000 per kg which is considered tooexpensive; (3) promotion strategy is still limited on personal selling by word of mouth;(4) strategy is direct distribution to consumers, and (5) recommended strategy is tomaintain the label and the brand and introduce product to general public, encourageproducers not to make wine to maintain continuity of the sugar production, set priceaccording to production costs while considering purchasing power, maintain healthstandard, and do continuous promotional activities.